2020
DOI: 10.1007/s10669-020-09784-x
|View full text |Cite
|
Sign up to set email alerts
|

MCDA Index Tool: an interactive software to develop indices and rankings

Abstract: A web-based software, called MCDA Index Tool (https ://www.mcdai ndex.net/), is presented in this paper. It allows developing indices and ranking alternatives, based on multiple combinations of normalization methods and aggregation functions. Given the steadily increasing importance of accounting for multiple preferences of the decision-makers and assessing the robustness of the decision recommendations, this tool is a timely instrument that can be used primarily by non-multiple criteria decision analysis (MCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 75 publications
0
27
0
Order By: Relevance
“…Third, the performance matrix was normalized using one of the eight possible normalization techniques. The normalization techniques include the rank, percentile rank, standardized, min-max, logistic, categorical (-1,0,1), categorical (0.1,0.2,0.4,0.6,0.8,1), and target methods [29]. The outcome of the CI-based procedure can ultimately weigh or rank the SNDA and identify which algorithms are best suited for the classification problem in question.…”
Section: Evaluation Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Third, the performance matrix was normalized using one of the eight possible normalization techniques. The normalization techniques include the rank, percentile rank, standardized, min-max, logistic, categorical (-1,0,1), categorical (0.1,0.2,0.4,0.6,0.8,1), and target methods [29]. The outcome of the CI-based procedure can ultimately weigh or rank the SNDA and identify which algorithms are best suited for the classification problem in question.…”
Section: Evaluation Methodologymentioning
confidence: 99%
“…Fourth, the scores assigned after the normalized process are combined using a particular aggregation function to generate an index for each alternative (i.e., algorithm). These aggregation functions include additive, geometric, harmonic, minimum, and median functions [29]. Fifth, indices assigned to different algorithms are used to assign ranks to these algorithms.…”
Section: Evaluation Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this challenge, the model-based approach has been introduced to systematically select attributes that cover the concerns and values of the problem under consideration. Accordingly, a few studies provide model-driven attributes by formulating the selection process of attributes as a choice problem (Cinelli et al 2020;Höfer et al 2020;Otto et al 2018;Rossberg et al 2017;Dale et al 2015;. Regardless of the source of the alternative pool, these studies evaluate candidate attributes based on properties of the desired attribute and apply a systematic process to select the attribute set.…”
Section: Current Approaches Towards the Selection Of Attributesmentioning
confidence: 99%
“…They found that FEW systems can be significantly impacted by labor shortages, and that food systems were more resilient compared to water and energy systems. Cinelli et al ( 2021 ) developed a MCDA tool and demonstrated a case study assessing the energy security and sustainability of various energy alternatives. The tool is available online for non-experts to use and includes various visualization and sensitivity analysis features.…”
mentioning
confidence: 99%